2008 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--4055
|View full text |Cite
|
Sign up to set email alerts
|

A Day Camp For Middle School Girls To Create A Stem Pipeline

Abstract: The College of Engineering at the University of Arkansas hosted an Engineering & Science Summer Day Camp for girls, July 30-Aug 3, 2007. This camp was initiated by two teachers involved in pre-engineering programs at Springdale High School. The teachers are involved in Project Lead the Way initiatives and approached the University about forming a potential pipeline that begins at the middle school level with the students proceeding to the preengineering program in their local high school and eventually pursuin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The duration of a robotic camp and length of sessions are varied in the literature. Some of the robotics camp were one day long (Burket et al, 2008;Cannon et al, 2006) some of them were one week long (Murphy & Rosenblatt, 2000), some of them were two weeks long (Williams et al, 2008) and some of them held at weekends throughout the year (Krugman, 1998). Therefore, the designer can decide the duration of camp according to instructional objectives of the camp.…”
Section: Discussion On Camp Durationmentioning
confidence: 99%
See 3 more Smart Citations
“…The duration of a robotic camp and length of sessions are varied in the literature. Some of the robotics camp were one day long (Burket et al, 2008;Cannon et al, 2006) some of them were one week long (Murphy & Rosenblatt, 2000), some of them were two weeks long (Williams et al, 2008) and some of them held at weekends throughout the year (Krugman, 1998). Therefore, the designer can decide the duration of camp according to instructional objectives of the camp.…”
Section: Discussion On Camp Durationmentioning
confidence: 99%
“…Technology related summer camps were used to increase children's interest toward technology, computing, and engineering (Miller, Shearer, & Moskal, 2005). Some of these camps were especially for girls to increase their curiosity and interest toward STEM and also increase the possibilities of the engineering careers (Burket et al, 2008); while the design phase of the camps, career effect of a robotics camp was not foreseen and also the researcher did not investigate that career effect deeply. The career effect emerged when the researcher was investigating children's benefits from the camps.…”
Section: Careermentioning
confidence: 99%
See 2 more Smart Citations
“…The reports may also offer suggestions for other institutions for successful implementation or present statistical analysis for assessment purposes. 20,21,22,23 In many ways, this paper represents an extension of these publications that detail academic programs for girls in science and engineering. At present, more literature can be found that addresses the subject of how groups, including librarians, can have a role with influencing girls towards considering traditionally male dominated fields.…”
Section: Literature Reviewmentioning
confidence: 99%